A Hybrid Atomistic Approach for the Mechanics of Deoxyribonucleic Acid Molecules - Saavedra-Flores, E (Web Portal ASME (American Society of Mechanical Engineers), 2013)
The paper proposes a new modeling approach for the prediction and analysis of the mechanical properties in deoxyribonucleic acid (DNA) molecules based on a hybrid atomistic-finite element continuum representation. The model takes into account of the complex geometry of the DNA strands, a structural mechanics representation of the atomic bonds existing in the molecules and the mass distribution of the atoms by using a lumped parameter model. A 13-base-pair DNA model is used to illustrate the proposed approach. The properties of the equivalent bond elements used to represent the DNA model have been derived. The natural frequencies, vibration mode shapes, and equivalent continuum mechanical properties of the DNA strand are obtained. The results from our model compare well with a high-fidelity molecular mechanics simulation and existing MD and experimental data from open literature. © 2013 by ASME.